ANALYSIS OF THE INFLUENCE OF CORPORATE GOVERNANCE ON INVESTMENT EFFICIENCY OF PUBLIC COMPANIES IN INDONESIA - Gunawan Widjaja (CV. Adiba Aisha Amira, 2025)
Good Corporate Governance is a process that regulates and controls a company in improving its business by paying attention to stakeholders to achieve company goals. The application of good corporate governance principles within a company can improve the company's financial performance and make the company free from fraud and can increase the trust of stakeholders and the public. The problem that companies often face is a lack of professionalism in running a company. Implementation of Good Corporate Governance cannot be separated from talking to companies that have valid legal entities in accordance with the provisions of the Law. The higher the investment efficiency, the more efficient the use of cash or company assets in making an investment, so it can be said that the more efficient investment is made, the higher the impact on cash flow. Corporate Governance influences the investment efficiency of public companies in Indonesia as measured by ROA and ROE. The research results which show that there is a positive influence of GCG on financial performance (ROA and ROE) can be interpreted as meaning that the better the implementation of GCG in a company can result in the company's operational activities being more effective and efficient, which in turn will increase financial performance.